César Ceriani Cernadas y Mariana Espinosa (Comps.) Argentina evangélica. Estudios socioantropológicos sobre misiones e iglesias. Santiago del Estero: IDACOR CONICET-Universidad Nacional de Córdoba y Bellas Alas Editorial, 2018, 564 pp. - Guerrero Jiménez, Bernardo (Ciencias sociales y religión, 2019)
In the introduction to this voluminous text, the authors define the objective of this book: "To gather in the same publication those works that symbolize, in their differences and congruences, the consolidation of a theme that was conceived in parallel to the construction of a field of multidisciplinary research "(2018: 16). It is no coincidence that in times of dictatorship, especially in Chile of the 1980s, appeared a group of sociologists of religion interested, above all, in seeing how religious discourses served as a source of legitimation of the dictatorship of Pinochet. The charm that evangelicals produced with their Te Deum, forced us to dust off Lalive's classic book from 1968. In Argentina the course was somewhat different, but there are interesting crossings.